Where the wild things are - Sendak, Maurice ([New York] : HarperCollins, 1984)
After he is sent to bed without supper for behaving like a wild thing, Max dreams of a voyage to the island where the wild things are.
Wilson's Children, October 2006
Elem. School Library Collection, June 2000
Book Links (A.L.A.), July 2006
Child Study Children's Book Committee, June 2002
Library Journal, March 2002
Horn Book, August 2007
Keywords: Dreams -- Fiction; Dreams -- Fiction